European (networked) agencies between independence and influence. Issue 10 (3rd October 2022) - Ruffing, Eva
ABSTRACT: European agencies' de facto independence and influence are phenomena, which are still undertheorized and understudied. In particular broader comparisons are lacking. This article compares six regulatory agencies and argues that their role in agenda-setting (as formal or informal agenda-setter) and the degree to which agencies can draw on the resources of their networks is decisive for their actual influence and independence. The article compares formal an informal agenda-setters, arguing that formal agenda-setters face a trade-off between independence and influence, whereas informal agenda-setters do not, with the networked character of agencies being a central intervening variable. As a result, it demonstrates that agenda-setting role and reliance on networks are central factors in explaining agencies' influence and independence in European decision-making.